An alternatingly amphiphilic, resistance-resistant antimicrobial oligoguanidine with dual mechanisms of action. (August 2021) - Chen, Zhiyong; Zhou, Cailing; Xu, Yangfan; Wen, Kang; Song, Junfeng; Bai, Silei; Wu, Chenxuan; Huang, Wei; Cai, Qingyun; Zhou, Kai; Wang, Hui; Wang, Yingjie; et al.
Abstract: The increasing number of infections caused by multi-drug resistance (MDR) bacteria is an omen of a new global challenge. As one of the countermeasures under development, antimicrobial peptides (AMPs) and AMP mimics have emerged as a new family of antimicrobial agents with high potential, due to their low resistance generation rate and effectiveness against MDR bacterial strains resulted from their membrane-disrupting mechanism of action. However, most reported AMPs and AMP mimics have facially amphiphilic structures, which may lead to undesired self-aggregation and non-specific binding, as well as increased cytotoxicity toward mammalian cells, all of which put significant limits on their applications. Here, we report an oligomer with the size of short AMPs, with both hydrophobic carbon chain and cationic groups placed on its backbone, giving an alternatingly amphiphilic structure that brings better selectivity between mammalian and bacterial cell membranes. In addition, the oligomer shows affinity toward DNA, thus it can utilize bacterial DNA located in the vulnerable nucleoid as the second drug target. Benefiting from these designs, the oligomer shows higher therapeutic index and synergistic effect with other antibiotics, while its low resistance generation rate and effectiveness on multi-drug resistant bacterial strains can be maintained. We demonstrate that this alternatingly amphiphilic, DNA-binding oligomer is not only resistance-resistant, but is also able to selectively eliminate bacteria at the presence of mammalian cells. Importantly, the oligomer exhibits good in vivo activity: it cleans all bacteria on Caenorhabditis elegans without causing apparent toxicity, and significantly improves the survival rate of mice with severely infected wounds in a mice excision wound model study.